Mesenchymal Cystic Hamartoma Presenting with Spontaneous Pneumothorax - J Glezos; D Toppin; T Cooney (Canadian Respiratory Journal)
A 53-year-old woman presented with a spontaneous right-sided pneumothorax. Computed tomography chest scan demonstrated a large bulla involving the right middle lobe. Recurrence of the pneumothorax after initial closed chest tube drainage necessitated thoracotomy and wedge resection. Histopathological examination revealed features consistent with a benign mesenchymal cystic hamartoma. Pneumothorax is a recognized complication of mesenchymal cystic hamartoma, a lesion that also has malignant potential.